REPRESENTATION OF THE DISMISSED KPK EMPLOYEES IN THE JAKARTA POST ARTICLES (Representasi Pegawai KPK yang Diberhentikan pada Artikel The Jakarta Post) - Ai Yeni Yuliyanti; Ponia Mega Septiana; Titania Sari; Busro Busro (SAWERIGADING, 2021)
This qualitative study analyzes the strategy used by The Jakarta Post to represent the dismissed KPK employees in the case of their failure in the Civic test as an employment status transition within the antigraft body and its representation. The researchers use Critical Discourse Analysis specifically the Social Actor Representation (SAR) theory from Theo Van Leeuwen (2008). It is supported by Richardson's (2007) theory to analyze the text producer’s lexical choice and the transitivity theory of Halliday and Matthiessen (2004) to analyze role allocation. This study shows that The Jakarta Post represents the dismissed KPK employees' both exclusion and inclusion strategy, but inclusion is dominant. The dismissed KPK employees are represented negatively. It is shown from the lexical choice used through the words ‘dismiss’, ‘fire’, and ‘fail’ to represent them. The Jakarta Post also uses other strategies: classification and individualization and collectivism.